2015
DOI: 10.1016/j.elspec.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum beats at the metal/organic interface

Abstract: Time resolved two-photon photoemission (TPPE) is used to probe the unoccupied electronic structure of monolayer films of dicarbonitrile-quaterphenyl (NC-Ph 4-CN) on Ag(111) and cobalt phthalocyanine (CoPc) on Ag(100). For both samples, photoelectron spectra show a well-formed series of electronic states near the vacuum level. These are assigned as the 1 ≤ n ≤ 4 image-potential states (IPS's) based on the scaling of their binding energies and lifetimes. Time domain measurements at energies near the vacuum level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 73 publications
(56 reference statements)
1
24
0
Order By: Relevance
“…In a previous 2PP experiment on Ag (111) surface where femtosecond laser excitation was tuned through ENZ, we observed the same feature, and concluded that it could not be attributed to an excited-state population-dependent Auger decay, because it appeared with comparable intensities relative to other features with nanosecond and femtosecond laser pulse excitations. 75 Instead, because its onset coincided with the longitudinal plasmon frequency, we assigned it to a collective process where light interaction induces an internal plasmon field, locking the 2PP signal to 2ℏω p .…”
Section: ■ Plasmonic Photoemissionsupporting
confidence: 64%
See 4 more Smart Citations
“…In a previous 2PP experiment on Ag (111) surface where femtosecond laser excitation was tuned through ENZ, we observed the same feature, and concluded that it could not be attributed to an excited-state population-dependent Auger decay, because it appeared with comparable intensities relative to other features with nanosecond and femtosecond laser pulse excitations. 75 Instead, because its onset coincided with the longitudinal plasmon frequency, we assigned it to a collective process where light interaction induces an internal plasmon field, locking the 2PP signal to 2ℏω p .…”
Section: ■ Plasmonic Photoemissionsupporting
confidence: 64%
“…52,77 The "2ℏω p " feature could only be attributed to the collective plasmon response, and was supported by the occurrence of a similar signal for the Ag(100) surface. 75 In fact, this 2ℏω p peak has been observed in the 2PP spectra of Ag (111) and (100) surfaces for excitation with ℏω L ≥ ℏω p , but its nonband structure and collective origin led to its misassignment, or neglect. 82,84−86 In the following, by reasoning that the 2ℏω p feature represents a nearly isotropic bulk plasmonic response, we reexamine the plasmonic photoemission of Ag (111) and Ag(100) surfaces, and explore it for Ag (110) surface for ℏω L ≥ ℏω p .…”
Section: ■ Plasmonic Photoemissionmentioning
confidence: 99%
See 3 more Smart Citations